2021
DOI: 10.3389/fneur.2021.684791
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamic Correlates of Transcutaneous Auricular Vagal Nerve Stimulation in Consciousness Restoration: An Open-Label Pilot Study

Abstract: This study aimed to preliminarily illustrate the cerebral hemodynamic correlates of transcutaneous auricular vagal nerve stimulation (taVNS) in consciousness restoration. Arterial spin labeling (ASL) was adopted with functional magnetic resonance imaging (fMRI) to measure cerebral blood flow (CBF) changes before and after taVNS in 10 qualified patients with disorders of consciousness (DOC). Before taVNS, five patients responded to auditory stimuli (RtAS), and five did not respond to auditory stimuli (nRtAS). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 65 publications
(87 reference statements)
4
43
0
Order By: Relevance
“…This has been replicated in t-VNS functional imaging studies which have confirmed stimulation and increased CBF at vagally innervated brain regions during auricular t-VNS and notably decreased perfusion at hippocampal regions ( Kraus et al, 2007 , 2013 ; Frangos and Komisaruk, 2017 ). T-VNS has also demonstrated efficacy in increasing arousal in comatose patients who respond to auditory signaling and again the brain regions noted on fMRI to be activated were similar to previous iVNS studies, including left superior temporal gyrus, left prefrontal cortex, left insular cortex, left middle frontal gyrus among other cortical and subcortical structures ( Yu et al, 2021 ).…”
Section: Mechanism Of Action: Vagus Nerve Stimulation Increases Cereb...supporting
confidence: 79%
“…This has been replicated in t-VNS functional imaging studies which have confirmed stimulation and increased CBF at vagally innervated brain regions during auricular t-VNS and notably decreased perfusion at hippocampal regions ( Kraus et al, 2007 , 2013 ; Frangos and Komisaruk, 2017 ). T-VNS has also demonstrated efficacy in increasing arousal in comatose patients who respond to auditory signaling and again the brain regions noted on fMRI to be activated were similar to previous iVNS studies, including left superior temporal gyrus, left prefrontal cortex, left insular cortex, left middle frontal gyrus among other cortical and subcortical structures ( Yu et al, 2021 ).…”
Section: Mechanism Of Action: Vagus Nerve Stimulation Increases Cereb...supporting
confidence: 79%
“…TaVNS can also clinically significantly improve depression, anxiety, and drive symptoms in patients with TRD (24). Meanwhile, taVNS has been used for MDD and other disorders such as insomnia (25), disorders of consciousness (26), epilepsy (27), and migraine (28). However, the immediate brain effects of taVNS on TRD are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Together these studies (presented in Table 1) suggest that although promising as a DoC treatment, taVNS may not hold equal promise for all. A study by Yu et al (2021) presents an important step in determining the characteristics of responders. Out of 10 patients (seven UWS and three MCS) it turned out that only those who reacted to auditory stimuli during the CRS-R examination benefited from taVNS, as evidenced by behavioral and neuroimaging data.…”
Section: Vagus Nerve Stimulation and Transcutaneous Auricular Vagus N...mentioning
confidence: 99%